2023
DOI: 10.3390/biomedicines11082155
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Comparison of the Mechanical Properties of 3D-Printed Resin through Triple-Jetting Technology and Conventional PMMA in Orthodontic Occlusal Splint Manufacturing

Ioan Barbur,
Horia Opris,
Bogdan Crisan
et al.

Abstract: Dental 3D-printing technologies, including stereolithography (SLA), polyjet (triple-jetting technology), and fusion deposition modeling, have revolutionized the field of orthodontic occlusal splint manufacturing. Three-dimensional printing is now currently used in many dental fields, such as restorative dentistry, prosthodontics, implantology, and orthodontics. This study aimed to assess the mechanical properties of 3D-printed materials and compare them with the conventional polymethylmethacrylate (PMMA). Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…The research protocol was approved by the Ethics Committee of "Iuliu Hatieganu" University of Medicine and Pharmacy Cluj-Napoca and was registered under the number 253/13.09. 22.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research protocol was approved by the Ethics Committee of "Iuliu Hatieganu" University of Medicine and Pharmacy Cluj-Napoca and was registered under the number 253/13.09. 22.…”
Section: Methodsmentioning
confidence: 99%
“…This can be performed by replacing the conventional waxed restoration with 3D printed ones by using the pressing technique. The fact is sustained by newest trends indicating CAD-CAM printing as a more effective fabrication technological process of composite parts destined to dental applications [21,22]. Thus, the purpose of our study consisted of comparing the marginal adaptation of LD (E-Max) crowns fabricated via CAD-CAM technology with 3D printing-pressing (3D Asiga Max, Sydney, Australia) and classical milled crowns using SEM.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports indicate that, for the moment, the mixes of PMMA compatible with VPP 3D printing techniques are for dental technologies and implants [135][136][137], although a few studies have reported additional medical uses [138]. The notable characteristics of PMMAbased constructs include their good aesthetics, physicochemical properties, low cost, excellent biocompatibility, low toxicity, reliability, and good mechanical strength [130,132,133].…”
Section: Poly(methyl Methacrylate)mentioning
confidence: 99%
“…This customization effectively surrounds the residual bone and enhances its integration with the implant [38]. The efficacy of the customized 3D implant has been demonstrated in the successful treatment of maxillofacial bone defects [47,48]. Moreover, efforts have been made to extend its application to the repair of alveolar bone, thereby improving tooth rehabilitation outcomes [49].…”
Section: D Printing In Orthognathic and Oral Maxillofacial Surgerymentioning
confidence: 99%